Effect of Spacing on Growth and Increment of Hardwickia binata Roxb. in Semi Arid Region of Rajasthan - mohamed, M. B. Noor; A, Keerthika; Gupta, Dipak Kumar; Chaudhary, Kamla K.; Shukla, A. K.; Jangid, B. L. (International Journal of Economic Plants, 2018)
Spacing is one of the most important considerations in plantations to avoid the competition and effective utilization of resources among the agricultural crops and trees. The present experiment was conducted to determine the effect of spacing on growth and increment of 30-year old Hardwickia binata Roxb. at Central Arid Zone Research Institute (CAZRI), Regional Research Station, Pali-Marwar which is located between 25°47’- 25°49’ E and 73°17’-73°18’ N at 217-220 m MSL. Two tree spacing i.e. closer spacing (666 tree ha-1 with 5×3 m2 spacing) and wider spacing (333 tree ha-1 with 10×3 m2 spacing) were adopted with Randomized Block Design and replicated twice. Results exhibited significant effect of spacing on the growth and yield of the trees in Hardwickia binata plantation. Among the different spacing regimes, wider spacing of 3×10 m2 resulted better tree height, DBH, tree circumferences, number of branches, clear bole height, crown width, crown length and tree volume. In general, DBH, tree circumference, crown width and crown length and tree volume is more in wider spacing with less tree density while lesser in closer spacing with high tree density. But there is not much differences in tree height and number of branches between two different spacing. Therefore, this study indicates that the increased spacing between the Hardwickia binata trees resulted better growth and increment compared to closer spacing.